STATE SUPPORT OF SCIENTIFIC RESEARCH IN RUSSIA – LOSSES, ACHIEVEMENTS AND PROBLEMS - A. Fedotov; N. Vasetskaya (Модернизация, инновация, развитие)
In the present research paper the goals, tasks and main indicators of realization of the Federal Target Program (FTP) “Research and development according priority directions of elaboration of the science and technology unit of Russia” for 2007–2013 and 2014–2020 years are analised. The main goal of the paper is analysis of the correctness of the goals formation and the structure of the corresponding tasks in mentioned above Federal Programs, investigation of the macroeconomic results of the realization of both programs and evaluation of possible reasons, which are infl uence to the results of programs implementation and state support for scientific research efficiency. In the present paper the analysis of the reached and planed results of the described FTP is presented. The new system for increasing the effectiveness of both FTP goals and tasks is proposed. Goal’s markers of both FTP realization are investigated. The more correct system for results evaluation of the scientific, technology and innovation activity according FTP is proposed. The application of the proposed system of goals and tasks would provide significant results for development strategy evaluation for promising directions of the scientific and innovation activity of the institution, realization of federal target programs and calling in business for development of innovation activity of the universities and scientific institutions.